The utilitarian foundations of the economic approach to human behavior (2005)
The economic approach to the study of human behavior has been presented by its foremost representative as the most effective method of studying social phenomena. Gary Becker's view supposes that, on the one hand, all social phenomena can be explained as a consequence of individual actions and, on the other, there is a stable pattern of individual behavior economics has been able to understand thoroughly. Hence, economics, according to this view, is no longer limited to the study of a certain domain of human actions or to the understanding of material wealth or the necessary conditions for the material reproduction of society. Economics is a method that gives the social scientist the necessary tools to understand and even transform the world that surrounds him/her. Becker clearly acknowledges the direct link between his approach and Jeremy Bentham's theory. Beyond the apparent connections regarding their conception of human nature there is one central point that links the two authors: their view of economics as an attitude of the human mind, an inherent capacity to calculate that explains all human actions. This paper argues that Bentham provides the philosophical groundings for Becker's theory. The application of the principle of utility to every aspect of human behavior justifies economic imperialism by transforming economics into a method of general analysis of human behavior. Indeed, economics is no longer defined according to its subject matter but according to its method, which means an increasing scope explaining Becker's claim that the economic approach provides a rigorous framework for the analysis of all social phenomena.